Increasing boreal fires reduce future global warming and sea ice loss - Edward Blanchard-Wrigglesworth; Patricia DeRepentigny; Dargan M. W. Frierson (Proceedings of the National Academy of Sciences, 2025)
Biomass burning can affect climate via the emission of aerosols and their subsequent impact on radiation, cloud microphysics, and surface and atmospheric albedo. Biomass burning emissions (BBEs) over the boreal region have strongly increased during the last decade and are expected to continue increasing as the climate warms. Climate models simulate aerosol processes, yet historical and future Coupled Model Intercomparison Project (CMIP) simulations have no active fire component, and BBEs are prescribed as external forcings. Here, we show that CMIP6 used future boreal BBEs scenarios with unrealistic near-zero trends that have a large impact on climate trends. By running sensitivity experiments with ramped up boreal emissions based on observed trends, we find that increasing boreal BBEs reduces global warming by 12% and Arctic warming by 38%, reducing the loss of sea ice. Tropical precipitation shifts southward as a result of the hemispheric difference in boreal aerosol forcing and subsequent temperature response. These changes stem from the impact of aerosols on clouds, increasing cloud droplet number concentration, cloud optical depth, and low cloud cover, ultimately reducing surface shortwave flux over northern latitudes. Our results highlight the importance of realistic boreal BBEs in climate model simulations and the need for improved understanding of boreal emission trends and aerosol–climate interactions.